Pertanggung Jawaban Pidana Terhadap Penelentaran Isteri Oleh Suami yang Sah: Studi di Kec. Medan denai - Erni Elvisyahri; Ismail Koto (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Society still considers cases of violence that occur within the family as a private matter that should not be involved by outsiders, not only domestic violence is the main problem but also with the issue of neglect that occurs within the family, the problem is also very broad, not only regarding livelihoods. it is not appropriate, there is also a problem, namely being a drug addict, so the problem of neglect is the same as domestic violence which often occurs recently, in Law No. 23 of 2004 concerning the Elimination of Domestic Violence (PDKRT) it is prohibited to abandon people within the scope of their household, even though according to the law that applies to him or because of an agreement or agreement he is obliged to provide life, care or maintenance to that person. Based on Article 49 letter a of the PKDRT Law (Elimination of Domestic Violence). And the Criminal Code also explains that the husband's act of entering into a polygamous marriage without court permission is a criminal offense as regulated in Article 279 of the Criminal Code. The research objective used in this journal is empirical juridical research, namely research that aims to combine research using books or laws and is carried out using interview methods which aim to add to the journal's research. The crimes that have occurred so far have started from the smallest environment, namely the family or household, to the larger environment, namely society. Abandoning one's household is a bad and disgraceful act, in the view of the general public, people who abandon their family are considered to have committed a disgraceful act and socially they will receive sanctions in the form of a despicable label on the perpetrator of the neglect. Keywords: Neglect, Criminal Liability, By legal husband